Behavior of Column Reinforced UHPFRC Materials using Excentric Loading - Siahaan, Ruth Navratilova; Tarigan, Johanes; Bakar, Badarol Hisham Abu; Nursyamsi, Nursyamsi (ASTONJADRO, 2025)
Column is part of reinforced concrete which has a function as a support. However, columns are often damaged by earthquakes. Damage to the column results in the need for treatment to improve the quality of the column. One way that can be done to repair the column is by providing a layer of UHPFRC reinforcement to the damaged column. UHPFRC is a concrete that has very high quality. Research on the UHPFRC continues today to get updates on the advantages of UHPFRC. In this study, the columns used were 4 samples. One sample is used as a control column which is tested by loading until it collapses and the remaining 3 samples will be reinforced with various variations of UHPFRC thicknesses of 10, 15 and 20 mm. The column is first given a load of 50% of the maximum load of the control column. The loading given to the column with eccentric loading is 175 mm. The results of laboratory tests carried out by compression testing showed that the reinforced column experienced an increase in maximum load compared to the control column. The maximum load on the control column (CC) is 17.79 kN, while the column with 10 mm thick UHPFRC (RT-C1) is 49.80 kN, the column with 15 mm thick UHPFRC is 59.60 kN and the column with 20 mm thick UHPFRC of 69.80 kN. The maximum load capacity increase in the reinforced column compared to the control column is RT-C1 55.63%; RT-C2 86.25% and RT-C3 118.13%. As a result of the load received on the column, resulting in shortening towards the vertical. The shortening that occurs in the control column (CC) is 17.79 mm; RT-C1 at 17.95mm; RT-C2 of 18.51 mm and RT-C3 of 19.84 mm. The results of this study indicate that UHPFRC can be used as a reinforcement material for reinforced concrete columns.